2022
DOI: 10.4062/biomolther.2022.077
|View full text |Cite
|
Sign up to set email alerts
|

Loganin Prevents Hepatic Steatosis by Blocking NLRP3 Inflammasome Activation

Abstract: Activation of the NLRP3 inflammasome is a necessary process to induce fibrosis in nonalcoholic fatty liver disease (NAFLD). Nonalcoholic steatohepatitis (NASH) is a kind of NAFLD that encompasses the spectrum of liver disease. It is characterized by inflammation and ballooning of hepatocytes during steatosis. We tested whether inhibiting the NLRP3 inflammasome could prevent the development and pathology of NASH. We identified loganin as an inhibitor of the NLRP3 inflammasome and investigated whether in vivo ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Jang et al reported that loganin could block NLRP3 activation in hepatic steatosis. 22 Choi et al suggested that loganin relieved gout inflammation through inhibiting activation of NLRP3 inflammasome. 14 Moreover, Zhang et al showed loganin could attenuate lung injury induced by sepsis through repressing NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al reported that loganin could block NLRP3 activation in hepatic steatosis. 22 Choi et al suggested that loganin relieved gout inflammation through inhibiting activation of NLRP3 inflammasome. 14 Moreover, Zhang et al showed loganin could attenuate lung injury induced by sepsis through repressing NLRP3 inflammasome-mediated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al reported that loganin could block NLRP3 activation in hepatic steatosis 22 . Choi et al suggested that loganin relieved gout inflammation through inhibiting activation of NLRP3 inflammasome 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Loganin, a type of bioactive iridoid glycoside extracted from traditional Chinese medicine, commonly called Cornus officinalis, was established to have potent anti-depression, neuropathic protection, and anti-inflammation effects (82)(83)(84). Yuan et al reported that loganin could prominently alleviate the pathologic alterations of DSS-induced colitis, increase the tight junction proteins to protect the intestinal epithelial barrier, and inhibit the expression of colonic pro-inflammatory cytokines such as IL-1b, IL-6, and TNF-a (85).…”
Section: Loganinmentioning
confidence: 99%